PEMANFAATAN LIMBAH URIN SAPI MENJADI BIOURIN SEBAGAI PUPUK ORGANIK CAIR DI DESA COT CUT KECAMATAN KOTA BARO KABUPATEN ACEH BESAR - Masyitah Masyitah; D Yana; G Ambartiarsari (LP4MK STKIP PGRI Lubuklinggau, 2023)
Community service was carried out in Cot Cut Village, Kota Baro Subdistrict, Aceh Besar Regency. Waste management of a livestock business that is not good and correct will cause unpleasant odors in the environment around the farm. Cow urine waste has the potential to be used as liquid organic fertilizer as well as other benefits of cow urine fertilizer as a Growth Regulator (ZPT). This community service program aims to provide knowledge and skills of farmers/community in utilizing cow urine waste processed into biourin products as liquid organic fertilizer. The method used is counseling and demonstration. The results achieved in this activity are that farmers are motivated to make liquid organic fertilizer from cow urine waste into biourin products which previously the waste was wasted without further processing. Farmers/communities gained knowledge and skills on the technique of processing cow urine into biourine so that it can be used in supporting agricultural cultivation activities and become an additional source of income for farmers/communities.